2006
DOI: 10.1186/1479-5876-4-6
|View full text |Cite
|
Sign up to set email alerts
|

Disaggregation and invasion of ovarian carcinoma ascites spheroids

Abstract: Background: Malignant ascites often develops in advanced stages of ovarian carcinoma, consisting of single and aggregated tumor cells, or spheroids. Spheroids have commonly been used as tumor models to study drug efficacy, and have shown resistance to some chemotherapies and radiation. However, little is known about the adhesive or invasive capabilities of spheroids, and whether this particular cellular component of the ascites can contribute to dissemination of ovarian cancer. Here, we examined the invasive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 37 publications
5
73
1
Order By: Relevance
“…Interestingly, we found that acute treatment of these cells with Cisplatin at 1uM for 24 hours also resulted in a reduction of BMP Smad phosphorylation, and when combined with DMH1 eliminated the remaining detectable phosphorylated Smads 1,5 and 9 (Figure 2A). When ovarian cancer metastasizes, it can form spheroids that can invade and travel to distant sites [39; 40]. To mimic this phenomenon in vitro , cancer cells can be grown as spheroids using ultra-low adhesion cell culture plates.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we found that acute treatment of these cells with Cisplatin at 1uM for 24 hours also resulted in a reduction of BMP Smad phosphorylation, and when combined with DMH1 eliminated the remaining detectable phosphorylated Smads 1,5 and 9 (Figure 2A). When ovarian cancer metastasizes, it can form spheroids that can invade and travel to distant sites [39; 40]. To mimic this phenomenon in vitro , cancer cells can be grown as spheroids using ultra-low adhesion cell culture plates.…”
Section: Resultsmentioning
confidence: 99%
“…38 In particular, spheroid models mimic the microenvironment of avascular solid tumors and in the case of EOC, naturally formed spheroids are abundant in ascitic fluid. [39][40][41][42] It has also been demonstrated that it is possible to grow large numbers of 3D spheroids from tumorexplanted cells thus determining chemoresponse diversity in a large array of samples originating from single source tumor. 42,43 Moreover, due to the geometric, dimensional, and functional homologies between spheroids and solid tumor biopsy sections, assay methods performed on spheroids may be more easily extended to tissue microsections.…”
Section: Empirical Chemosensitivity Testing In a Spheroid Model Of Ovmentioning
confidence: 99%
“…Previously, several groups [8][9][10][11][12][13][14] had used endpoint assays to show that ovarian cancer cells attach to and invade into mesothelial cell monolayers. This assay is unique in that it uses fluorescently labeled cells to distinguish tumor cells from mesothelial cells, so that the dynamics of these two cell populations can be monitored throughout the assay.…”
Section: Movie 3 Control Ovca433 Spheroids (Red) Invading Into a Mesmentioning
confidence: 99%
“…Our protocol was adapted from previously described methods for analyzing ovarian tumor cell interactions with mesothelial monolayers [8][9][10][11][12][13][14][15][16] , and was first described in a report showing that ovarian tumor cells utilize an integrin -dependent activation of myosin and traction force to promote the exclusion of the mesothelial cells from under a tumor spheroid 17 . This model takes advantage of time-lapse fluorescence microscopy to monitor the two cell populations in real time, providing spatial and temporal information on the interaction.…”
mentioning
confidence: 99%